Pengembangan Media Pembelajaran Pengaplikasian Arduino Sebagai Media Pengenalan dan Pengukuran Komponen Elektronika Berbasis Mikrokontroler Arduino - Agus Faiz Fahruddin; Agus Adiarta; Nyoman Santiyadnya (Universitas Pendidikan Ganesha, 2022)
This study aims to develop Arduino Application Learning Media as a Media for the Introduction and Measurement of Arduino Microcontroller-Based Electronic Components that can be used to assist the learning process, to determine the feasibility of being used as a learning medium, and to find out the good response of students in Basic Electrical and Electronics subjects in the Program. Audio Video (TAV) Engineering Skills. This research includes the R&D (Research and Development) research model. The study used a questionnaire or questionnaire as an instrument of data collection by content experts, media experts, and students. From the research results obtained: the results of the media expert trial obtained a percentage value of 94.04% with a very feasible classification, the results of the Material expert trial obtained a percentage of 92.5% with a very feasible classification, the results of the small group test the lowest respondent value was at respondent 5 (R5) with a score of 58 is classified as very good, the results of the large group test result in the lowest respondent scores, namely respondents 13 (R13) and 15 (R15) with a score of 57 including very good classification. Based on the results of the study, the Arduino Microcontroller-Based Learning Media Introduction of Electronic Components is suitable for use in the learning process on Basic Electrical and Electronics subjects at the Audio Video (TAV) Expertise Program at SMK Negeri 1 Denpasar.